THE ROLES OF TEACHER TO PROMOTE CLASSROOM INTERACTION IN CHILDREN CLASSES - Kristi Nuraini (Universitas Muhammadiyah Gresik, 2015)
Classroom interaction is the collaborative exchange of thoughts, feelings, or ideas betweentwo or more people, resulting in a reciprocal effect on each other which takes place in theclassroom. It is a complete action where teacher is one of the elements to assist this fromhappening. In the children classes, where a lot of students are having considerably minorexposure of language, need extra attention to help interaction to take place. This articleaimed at contributing the teaching of English to young learners and promote the classroominteractions in children classes. The final section of this article proposes some techniqueson how to initiate and promote interactions in children classes.